Ethical perspectives on surveillance and preventive strategies for HIV/AIDS in South Africa - Koenane, Mojalefa Johannes (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil)-- University of Stellenbosch, 2000